Modelling beluga habitat use and baseline exposure to shipping traffic to design effective protection against prospective industrialization in the Canadian Arctic. Issue 3 (6th April 2018) - Pirotta, Enrico; New, Leslie; Marcoux, Marianne
Abstract: Global warming is predicted to reduce sea ice and thereby grant access to new shipping routes in the Arctic, leading to the expansion of human exploitation of natural resources in this region. The accompanying rise in boat numbers could impact the local populations of marine mammals by increasing collision rates and behavioural disturbance. It is therefore important to quantify the baseline exposure to current levels of shipping traffic and to understand how wildlife's important habitat overlaps with shipping lanes, in order to support appropriate spatial planning and management. In this study, telemetry tracks from nine belugas ( Delphinapterus leucas ) tagged in Western Hudson Bay, which is home to the world's largest summer aggregation of this species, were used to estimate the habitat use of the animals and to map any overlap with current shipping activities. Following a use–availability design, with spatially adaptive smooths fitted using generalized estimating equations, beluga habitat use was quantified, confirming that they aggregate in coastal areas in association with river estuaries. The baseline exposure is low, and is concentrated around major harbours in the region. Rising levels of traffic will increase anthropogenic pressure on Western Hudson Bay belugas. The approach presented here informs the design of effective spatial protection measures to minimize any potential consequence on the population.